Modeling interbasin groundwater flow in karst areas: Model development, application, and calibration strategy. (February 2020) - Nguyen, Van Tam; Dietrich, Jörg; Uniyal, Bhumika
Abstract: Karstification is considered as one of the most common reasons for interbasin groundwater flow (IGF). IGF in some karst areas could be significant such that it must be accounted for in hydrologic modeling. In this study, the Soil and Water Assessment Tool (SWAT) was modified to explicitly account for IGF in karst areas. The modified model uses two conceptual models to simulate hydrologic processes in karst and non-karst regions. The modified model was applied in the karst-dominated region in the southwest Harz Mountains, Germany. Multisite streamflow data and satellite-derived actual evapotranspiration (ETa) were used for model calibration. Results show that (1) the modified model can be satisfactorily calibrated and validated for streamflow and ETa (2) the model performance for ETa and streamflow at some gauging stations are highly correlated, and (3) the use of satellite-derived ETa does not affect the model performance. Highlights: SWAT was modified to simulate interbasin groundwater flow in karst and non-karst area. Multi-site streamflow data and satellite-derived ETa were used for model calibration. Model performances for ETa and for streamflow are highly correlated. The use of satellite-derived ETa (MOD16 ETa) does not affect the model performance.